Endothelin-1 down-regulates matrix metalloproteinase 14 and 15 expression in human first trimester trophoblasts via endothelin receptor type B - Majali-Martinez, Alejandro; Velicky, Philipp; Pollheimer, Jürgen; Knöfler, Martin; Yung, Hong wa; Burton, Graham J.; Tabrizi-Wizsy, Nassim Ghaffari; Lang, Uwe; Hiden, Ursula; Desoye, Gernot; Dieber-Rotheneder, Martina (Human reproduction (Oxford), 2017)
STUDY QUESTION Does endothelin-1 (ET-1) regulate matrix metalloproteinase (MMP) 14 and 15 production and invasion of human first trimester trophoblasts? SUMMARY ANSWER ET-1 in pathophysiological concentrations down-regulates MMP14 and MMP15 expression via endothelin receptor (ETR) type B and decreases trophoblast migration and invasion. WHAT IS KNOWN ALREADY MMP14 and MMP15 are involved in trophoblast invasion. Impairment of invasion has been linked to pregnancy complications such as pre-eclampsia (PE). ET-1 is up-regulated in PE. STUDY DESIGN, SIZE, DURATION In vitro study using primary human trophoblasts from 50 first trimester placentas (gestational week 7–12). PARTICIPANTS/MATERIALS, SETTING, METHODS Trophoblasts were cultured in the absence or presence of 10–100 nM ET-1. MMP14 and MMP15 mRNA and protein were quantified by RT-qPCR and Western blotting, respectively. Selective antagonists for ETRA (BQ-123) or ETRB (BQ-788) were used to identify ETR subtypes involved. Functional ET-1 effects were tested in first trimester chorionic villous explants and transwell invasion assays. The roles of tumor necrosis factor (TNF)-α (25 ng/ml) and oxygen (1%) in ET-1 regulation of MMP14 and 15 expression were assessed by Western blotting. MAIN RESULTS AND THE ROLE OF CHANCE ET-1 down-regulated MMP14 and MMP15 mRNA (−21% and −26%, respectively, P < 0.05) and protein levels (–18% and –22%, respectively, P < 0.05). This effect was mediated via ETRB. ET-1 decreased trophoblast outgrowth in placental explants (−24%, P < 0.05) and trophoblast invasion (−26%, P ≤ 0.01). TNF-α enhanced ET-1 mediated MMP15 down-regulation (by 10%, P < 0.05), whereas hypoxia abolished the effect of ET-1 on both MMPs. LARGE SCALE DATA N/A. LIMITATIONS, REASONS FOR CAUTION Only primary trophoblasts were used in this study. Since trophoblast yield from first trimester placental material is limited, further aspects of MMP14 and 15 regulation could not be characterized. Other anti-invasive factors may be altered by ET-1 in trophoblasts and, thus, contribute to the reduced invasion, but have not been investigated. Oxygen levels similar to those found in the decidua (5–8% O2) were not analyzed in this study. WIDER IMPLICATIONS OF THE FINDINGS ET-1 modifies placental function already during the first trimester of pregnancy, the time-window when the placental changes implicated in PE occur. Thus, our results improve the understanding of the placental mechanisms underlying trophoblast invasion and PE. STUDY FUNDING/COMPETING INTEREST(S) The study was funded by the Oesterreichische Nationalbank (Anniversary Fund, project number: 14796) and the Herzfelder'sche Familienstiftung (to J.P.; number: 00685). AMM received funding from the Austrian Science Fund FWF (W1241) and the Medical University Graz through the PhD Program Molecular Fundamentals of Inflammation (DK-MOLIN). The authors have no conflict of interest.